Effect of free trade area policy on innovation capability in the service industry - Qi Dong; Yuriy Bilan (Amfiteatru Economic Journal, 2024)
China has gradually established pilot free trade zones and implemented certain specific policies for its enterprises to deepen the economic system reform and expand the degree of market opening to the outside world. The establishment of a Free Trade Area exerts spillover effects and positive influences on import and export trade, synergistic regional development, and the ability to innovate of enterprises. However, in terms of policy, its role in enterprise innovation has not been explored. To explore the influence path of Free Trade Area Policy on the innovation ability of service industry companies, using the data of A-share listed companies in Shanghai and Shenzhen in the Guangdong Free Trade Area region from 2010 to 2021 and the Regression Discontinuity model, the micro mechanisms (intellectual property protection, equity incentives, and government subsidies) of the impact of the Free Trade Area Policy on the innovation capability of service industry companies were analysed. The results show that: (1) Intellectual property rights (IPR) protection and the innovation ability of service industry companies exhibit a U-shaped relationship. With the increase in IPR protection, the innovation ability of service industry companies first decreases and then increases. (2) Expanded equity incentive level internal gap increases the research and development (R&D) expenditures, but reduces the innovation capacity of service industry companies. (3) Government subsidies convey signals of innovation recognition to the market, reduce the business risks of service industry companies, and encourage improvements in innovation capability. The conclusions provide a theoretical basis and multi-dimensional ideas for service industry companies to improve their innovation capability. In addition, an empirical basis and reference is provided for the government administration of the Free Trade Area to evaluate the effectiveness of policy implementation, optimise the policy structure, improve the policy system, and promote Free Trade Area Policy.
Keywords: M21; D21; H71; 330; enterprise innovation capability; Free Trade Area Policy; Regression Discontinuity; service industry companies; Free Trade Area Policy; service industry companies; enterprise innovation capability; Regression Discontinuity